2012
DOI: 10.1007/s00394-012-0301-0
|View full text |Cite
|
Sign up to set email alerts
|

Garlic-derived S-allylmercaptocysteine is a hepato-protective agent in non-alcoholic fatty liver disease in vivo animal model

Abstract: PurposeTo investigate the hepato-protective properties and underlying mechanisms of SAMC in a non-alcoholic fatty liver disease (NAFLD) rat model.MethodsFemale rats were fed with a diet comprising highly unsaturated fat diet (30% fish oil) for 8 weeks to develop NAFLD with or without an intraperitoneal injection of 200 mg/kg SAMC three times per week. After euthanasia, blood and liver samples of rats were collected for histological and biochemical analyses.ResultsCo-treatment of SAMC attenuated NAFLD-induced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 35 publications
6
87
0
Order By: Relevance
“…It is well established that increased nitroxidative stress can be produced from impaired mitochondrial function (i.e., mitochondrial dysfunction), elevated levels of ethanol-inducible cytochrome P450-2E1 (CYP2E1) and other CYP isozymes, NADPH oxidases, inducible form of nitric oxide synthase (iNOS) and xanthine oxidase (XO) (Aubert, Begriche, Knockarert, Robin, & Fromenty, 2011;Lieber, 2004b;Spruss, Kanuri, Uebel, Bischoff, & Bergheim, 2011). On the other hand, the cellular levels of small-molecule antioxidants, such as glutathione (GSH), many vitamins including retinoic acid (vitamin A), thiamine (vitamin B1), ascorbic acid (vitamin C), and α-tocopherol (vitamin E), are known to be decreased following alcohol exposure (Cederbaum, 2012a;Leung & Nieto, 2013;Lieber, 1997;Nanji et al, 2003;Xiao et al, 2013) and/or under different pathophysiological conditions such as hypoxic liver injury and aging (Marí, Morales, Colell, García-Ruiz, & Fernández-Checa, 2009). Furthermore, recent data has shown that the activities of antioxidant enzymes such as glutathione peroxidase (Gpx), catalase, and superoxide dismutase (SOD) can be inhibited by alcohol and nonalcoholic substances (Abdelmegeed, Jang, Banerjee, Hardwick, & Song, 2013;Abdelmegeed, Moon, Chen, Gonzalez, & Song, 2010;Carmiel-Haggai, Cederbaum, & Nieto, 2005;Song et al, 2013).…”
Section: Pathological Mechanisms Of Liver Diseasesmentioning
confidence: 99%
“…It is well established that increased nitroxidative stress can be produced from impaired mitochondrial function (i.e., mitochondrial dysfunction), elevated levels of ethanol-inducible cytochrome P450-2E1 (CYP2E1) and other CYP isozymes, NADPH oxidases, inducible form of nitric oxide synthase (iNOS) and xanthine oxidase (XO) (Aubert, Begriche, Knockarert, Robin, & Fromenty, 2011;Lieber, 2004b;Spruss, Kanuri, Uebel, Bischoff, & Bergheim, 2011). On the other hand, the cellular levels of small-molecule antioxidants, such as glutathione (GSH), many vitamins including retinoic acid (vitamin A), thiamine (vitamin B1), ascorbic acid (vitamin C), and α-tocopherol (vitamin E), are known to be decreased following alcohol exposure (Cederbaum, 2012a;Leung & Nieto, 2013;Lieber, 1997;Nanji et al, 2003;Xiao et al, 2013) and/or under different pathophysiological conditions such as hypoxic liver injury and aging (Marí, Morales, Colell, García-Ruiz, & Fernández-Checa, 2009). Furthermore, recent data has shown that the activities of antioxidant enzymes such as glutathione peroxidase (Gpx), catalase, and superoxide dismutase (SOD) can be inhibited by alcohol and nonalcoholic substances (Abdelmegeed, Jang, Banerjee, Hardwick, & Song, 2013;Abdelmegeed, Moon, Chen, Gonzalez, & Song, 2010;Carmiel-Haggai, Cederbaum, & Nieto, 2005;Song et al, 2013).…”
Section: Pathological Mechanisms Of Liver Diseasesmentioning
confidence: 99%
“…Although some proposed pharmaceutical drugs have been extensively investigated in laboratory study, further tests and evaluations are necessary before applying clinically. In the past decades, several natural compounds are found to possess hepato-protective effects against the progression of NAFLD/NASH, including garlic [6], wolfberry [7], resveratrol [8], silibinin [9], coffee [10], and honey [11]. Due to their potent antioxidant and anti-inflammatory properties, these herbal derivatives hold promising prospects for future clinical application.…”
Section: Introductionmentioning
confidence: 98%
“…Garlic-derived S-allylmercaptocysteine (SAMC) exhibited hepatoprotective effect in nonalcoholic fatty liver disease (NAFLD) in rats (Xiao et al 2013 ). Co-treatment of SAMC attenuated NAFLD-induced liver injury, fat accumulation, collagen formation and free fatty acids (FFAs).…”
Section: Hepatoprotective Activitymentioning
confidence: 99%